The effectiveness of web-based learning in supporting the development of nursing students' practical skills during clinical placements: A qualitative study. (May 2019) - Barisone, Michela; Bagnasco, Annamaria; Aleo, Giuseppe; Catania, Gianluca; Bona, Massimo; Gabriele Scaglia, Stefano; Zanini, Milko; Timmins, Fiona; Sasso, Loredana
Abstract: Web-based learning, on its own or in combination with traditional teaching methods, has become a consolidated practice in many countries, and has been described as a valid and effective method that supports practical learning in undergraduate nursing students. The aim of this study was to explore the perception and effectiveness of web-based learning in facilitating the development of clinical skills in undergraduate nursing students. A qualitative descriptive study was conducted including online videos in three nursing schools of a university in Northern Italy. The participants were 26 undergraduate nursing students. A dedicated website was built including four videos and the respective checklists of four nursing techniques: insertion of a urinary catheter; insertion of a nasogastric tube; taking a blood sample; and the insertion of a peripheral intravenous line. Three Focus Groups were conducted, one for each nursing school. Thanks to its ease of use and unlimited access, web-based learning effectively supported students' clinical learning process by offering additional virtual visual support. Web-based learning could be effectively used to reduce the gap between theory and practice, and even as an upgrade for already qualified nurses. Highlights: Web-based learning in nursing is growing, but its use is still limited. Few studies have explored how web-based learning can improve clinical skills. Web-based learning impacts on patient safety and the quality of nursing practice.